Optimize BER Offset QPSK Baseband Modulation-Demodulation featuring AWGN and OFDM - Mohammad Hakim Adhiguna; Prapto Nugroho; Sigit Basuki Wibowo (Journal of Electrical, Electronic, Information, and Communication Technology, 2022)
In communication system, being fastest not always the best option because of much great error probabilities. Complex architecture also cost high for the component maintenances. An optimal OQPSK modem is provide for friendly use and affordable model in academic purposes. The proposed method is moderate way with twice data size than the conventional method, but error calculation is exactly constant. Good and optimal BER measurements from simulated binary data useful for academic learning purpose.